A novel vitamin K derived anticoagulant tolerant to genetic variations of vitamin K epoxide reductase - Chen, Xuejie (J Thromb Haemost, 2021)
BACKGROUND: Vitamin K antagonists (VKAs), such as warfarin, have remained the cornerstone of oral anticoagulation therapy in the prevention and treatment of thromboembolism for over half a century. They function by impairing the biosynthesis of vitamin K-dependent (VKD) clotting factors through the inhibition of vitamin K epoxide reductase (VKOR). The challenge of VKAs therapy is their narrow therapeutic index and highly variable dosing requirements, which are partially due to the genetic variations of VKOR. OBJECTIVES: The goal of this study was to search for an improved VKA that is tolerant to the genetic variations of its target enzyme. METHODS: A series of vitamin K derivatives with benzyl and related side-chain substitutions at the 3-position of 1,4-naphthoquinone were synthesized. The role of these compounds in VKD carboxylation was evaluated by mammalian cell-based assays and conventional in vitro activity assays. RESULTS: Our results showed that replacing the phytyl side-chain with a methylene cyclooctatetraene (COT) moiety at the 3-position of vitamin K(1) converted it from a substrate to an inhibitor for VKD carboxylation. Strikingly, this COT-vitamin K derivative displayed a similar inhibition potency in warfarin-resistant VKOR mutations whose warfarin resistance varied over 400-fold. Further characterization of COT-vitamin K for the inhibition of VKD carboxylation suggested that this compound targets multiple enzymes in the vitamin K redox cycle. Importantly, the anticoagulation effect of COT-vitamin K can be rescued with high doses of vitamin K(1). CONCLUSION: We discovered a vitamin K analogue that functions as a VKA, and is tolerant to genetic variations in the target enzyme.